APLIKASI MONITORING LABORATORIUM - Heri Siswanto; Yusapril Eka Putra; Rahmat Suhatmat (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2011)
Abstract Practicum is one part of the learning process in Politeknik Caltex Riau. Practicum in the laboratory usually uses electronic media, such as computer. In the laboratory, some students sometimes do not doing the practicum seriously. Occasionally, some students installing and running applications that do not fit with the experimental material. Because of that, in the laboratory required an application that can monitor student activities during the practicum activities in the laboratory. The aim of this project is to create an application that can monitoring what application  running by students during the practicum and to know the list of applications installed, log report and information on hardware and Windows Operating System that is used on the client computer. This desktop-based applications built with Visual Basic dot Net (VB.Net) and Microsoft SQL Server 2000 database. From the observations, this application suitable in practical activities requirement at the Polytechnic Caltex Riau because it can increase teaching and learning performance in the laboratory. In addition, the implementation of this application is useful for lecturers and laboratory users.Keywords: Monitoring, Visual Basic. Net, Micorosoft  SQL Server 2000